An analysis of the ethical codes and their applicability in the communication professions in Malaysia / Halimahton Shaari and Kiranjit Kaur - Shaari, Halimahton; Kaur, Kiranjit (Research Management Institute (RMI), 2012)
Studying media ethics and the ethical codes of the various media professions is an attempt to better understand the workings and conduct of the mass media which play a significant role in society. Like any other profession whose activities affect the public, the media too are bound by formal and informal controls. Part of the informal controls, codes of ethics, when formulated, were significantly influenced by the codes of more established media professions, particularly in the West. While taking a leaf out of the Western codes may give the local codes a more universal outlook, there is also concern that they may not adequately address the cultural and parochial realities that exist in this multiethnic society. Thus, this research hopes to study the suitability and applicability of the codes, not just in the context of multiculturalism, but also against international standards. Because of its informal nature, the codes of media ethics in Malaysia have been criticised as 'lacking punch'. Due to that, adherence to and observance of the codes is voluntary. A review of the codes and the findings may help the various professions to strengthen the codes and their utility; and subsequently lend some credibility and respectability to the media professions.